Code name Bananas - Walliams, David 1971- (HarperCollins Children's Books, 2020)
Go back in time with No. 1 bestselling author David Walliams for a whizz-bang epic adventure of action, laughter and secret plots - and the extraordinary friendship between a little boy and a huge gorilla that just might save the day... 1940. Britain is at war with Nazi Germany. Eleven-year-old Eric spends his days at the place that makes him most happy: London Zoo. And there's one animal in particular he loves: Gertrude the gorilla. With bombs falling all over London, Eric must rescue Gertrude. Together with his Uncle Sid, a keeper at the zoo, the three go on the run. But while hiding out at the seaside they uncover a top-secret Nazi plot... Join David Walliams on this action-packed, laugh-out-loud adventure for all the family!